Review: From Judgement to Passion. Devotion to Christ and the Virgin Mary, 800–1200 - Ward, Benedicta (The journal of theological studies, 2003)
From Judgement to Passion. Devotion to Christ and the Virgin Mary, 800–1200 Rachel Fulton Pp. xx+676 Frontispiece and 7 plates. New York Columbia University Press 2002 0 231 12550 x $ 40/£28